2012
DOI: 10.1159/000337094
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between HLA-A, HLA-B and HLA-DRB1 Allele Polymorphisms and Childhood Susceptibility to Acquired Aplastic Anemia

Abstract: To investigate the correlations between polymorphisms of human leukocyte antigen (HLA)-A, HLA-B and HLA-DRB1 alleles and childhood susceptibility to aplastic anemia (AA), 80 children with AA were investigated. Among the 80 children, 74 had severe AA (SAA). Blood samples were collected from 109 healthy children as the controls. High-resolution genotyping of HLA-A, HLA-B and HLA-DRB1 alleles was conducted using polymerase chain reaction amplification with sequence-specific primers and polymerase chain reaction a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…In addition, it has been shown that HLA-DRB1*15 is associated with the immunosuppressive therapy of children with AA (11,13,14); children who were positive for HLA-DRB1*15 exhibited a good response to the simple cyclosporine A (CsA) treatment and enhanced immunosuppressive therapy. However, previous studies concerning the association of HLA with AA in different provinces of China have yielded inconsistent results (15,16), and IST-related studies of HLA are limited.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been shown that HLA-DRB1*15 is associated with the immunosuppressive therapy of children with AA (11,13,14); children who were positive for HLA-DRB1*15 exhibited a good response to the simple cyclosporine A (CsA) treatment and enhanced immunosuppressive therapy. However, previous studies concerning the association of HLA with AA in different provinces of China have yielded inconsistent results (15,16), and IST-related studies of HLA are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Ethnic differences in genetic predisposition to AA risk appear to be shaped by HLA allele variations although it is difficult to draw definitive conclusions from specific ethnic group observations due to differences in the linkage disequilibrium existing between HLA alleles in different populations. Specific HLA allelotypes have been associated with the presence of PNH clones, 41,42 increased [43][44][45][46] or decreased 44,47 susceptibility to developing AA, and some others with response to IST. 41,44 The underlying pathophysiologic mechanism appears to be an induction of immune attack by activation of autoreactive cytototoxic T-cell clonotypes against HSCs in a HLA-restricted pattern.…”
Section: Immunog Ene Tic S Of Immune Dys Reg Ul Ationmentioning
confidence: 99%
“…Specific HLA allelotypes have been associated with the presence of PNH clones, 41,42 increased [43][44][45][46] or decreased 44,47 susceptibility to developing AA, and some others with response to IST. 41,44 The underlying pathophysiologic mechanism appears to be an induction of immune attack by activation of autoreactive cytototoxic T-cell clonotypes against HSCs in a HLA-restricted pattern. 48 Recent focus has also been on the impact of somatic acquired mutations in the HLA class genes on AA-related autoimmunity.…”
Section: Immunog Ene Tic S Of Immune Dys Reg Ul Ationmentioning
confidence: 99%
“…The HLA-DRB1∗07 allele has been reported overexpressed in AA patients with no difference between adults and children, placing it as a susceptible allele for AA, at least in that cohort of Iranian subjects [35]. In addition, other candidate alleles predisposing to AA and SAA in children have been reported such as HLA-B∗48:01, HLA-DRB1∗09:01, and HLA-B14 [41, 42]. However, in the latter study [42], it was demonstrated that different HLA associations occur in children and adults; therefore any assumptions regarding HLA allele distribution between these groups should be made cautiously.…”
Section: Aplastic Anemiamentioning
confidence: 99%
“…The allele HLA-DRB1∗13 appeared to be protective in SAA children of Turkish origin [43], as well as the HLA-DRB1∗03:01, HLA-DRB1∗11:01, and HLA-B∗51:01 alleles in Chinese children with AA [41]. Likewise, in a small cohort of Pakistani AA patients, HLA-DRB1∗03 had higher frequency in controls suggesting a putative protective role [33].…”
Section: Aplastic Anemiamentioning
confidence: 99%